Influence of Creative Problem Solving Model Interaction and Local Wisdom Approach to the Ability to Produce Literary Works - Arinah Fransori; Ade Siti Haryanti (Universitas Indraprasta PGRI, 2021)
Local wisdom has its own value and function in society. In addition, local wisdom is part of the culture in society which is an integral part of the language and society itself. In this case, how to explore the potential of local local wisdom and bring it up in a literary work. The purpose of this study was to determine and describe the effect of the local wisdom value approach and creative problem solving models on the ability to reproduce students' literary works. From the results of the study using a two-way analysis of variance with a significant level of 0.05, it was obtained that the F0 value was smaller than the Ftabel value, namely 0.039 <4.08 and sig. = 0.536> 0.05. There is a significant effect of creative problem solving models on the ability to produce literary works. From the results of the study using a two-way analysis of variance with a significant level of 0.05, the F0 value is greater than the Ftabel value, namely 5.635> 4.08 and sig. = 0.023 <0.05. There is a significant influence the local wisdom approach has on the ability to produce literary works. From the results of the study using a two-way analysis of variance with a significant level of 0.05, the F0 value is greater than the Ftabel value, namely 11.949> 4.08 and sig. = 0.001 <0.05.Keywords: local wisdom, creative problem solving models, reproduction of literary works